Taxation and Economic Growth in Nigeria - Nkwazema, Ogbonna, Gabriel; Cletus O, AMAH (International Journal on Economics, Finance and Sustainable Development, 2021)
In this study, we investigated two relevant types of taxation, namely: Custom and Excise Duty and Petroleum Profits Tax and how they relate to Nigeria Economic growth. The relationship between these two types of taxation and the Nigeria economic growth has become increasingly necessary because of the critical role they are expected to play in the Nigeria Economic Growth. The study adopted a descriptive and historical research design; secondary data for ten years (2009 -2018) were collected from various publications of the Central Bank of Nigeria (CBN) Statistical Bulletin and Annual Reports. Taxation as an independent variable was measured with Petroleum Profit Tax (PPT) and Custom and Excise Duties (CED) while the dependent variable was Economic Growth (EG) and the proxies were measured by the Gross Domestic Product (GDP). Analysis was performed on data collected using multiple Regressions. The results of the study showed that PPT and CED had significant relationships with economic development. In view of the findings, the study concludes that taxation is a strong socio-political and economic tool for economic development. Based on the findings and conclusion, this study recommends that government should ensure that revenue generated through taxation should be channeled towards infrastructural development and building capital stock to boost economic growth in Nigeria; government should also engage in a complete re-organization of administrative machinery of taxation in order to reduce incidence of tax avoidance and tax evasion to the barest minimum so as to improve the efficiency of taxation and bring more people and establishments into the tax net.